Peran Tokoh Agama Dalam Pencegahan Konflik di Tengah Masyarakat Multikultural Pada Era Digital - Novebri, Novebri; Pratiwi, Resdilla (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2021)
The goal of this research is to find out how religious leaders may help to avert conflict in a multicultural society. This study took place in Medan, Indonesia's North Sumatra Province. To conduct the study, the author employs a qualitative method in the form of a case study. Direct interviews with religious leaders from Islam, Christianity, Protestantism, Hinduism, Buddhism, Confucianism, religious organization leaders, and government officials were used to gather data. The Miles and Huberman approach was used to examine the interview data thematically. According to the findings of the study, religious leaders make three efforts to prevent conflict: I use online applications such as YouTube, Facebook, websites, and zoom meetings to disseminate religious teachings, and ii) using online applications such as youtube, Facebook, websites, and zoom meetings to disseminate religious teachings. iii) They hold regular meetings, both online and offline, to debate religious moderation and conflict prevention; iii) develop collaboration between religious harmony forums and security forces in the prevention of religious disputes. Religious leaders' involvement in a multicultural society plays a vital role in conveying information about religious moderation. Furthermore, the findings of this study show that religious leaders were successful in mediating religious moderation in order to create a moderate and tolerant community. Religious leaders' functions of monitoring and direction in conflict resolution are able to maintain religious moderation and avert disputes in Indonesia's multicultural society.